Management issues in Nigerian school librarianship: challenges for school librarians in the millennium (2007)
This paper revealed the complex nature of library management in general with particular reference to school library. The qualifies expected of a good school librarian were carefully listed. Also, the need for efficiency in school library administration was discussed while attempts were made to identify some managerial challenges ahead of the school librarian in the present millennium. Recommendations made are as follows: adequate funding should be provided by the founding institution; ICT facilities must be provided for Processing and dissemination of information; formulation of functional collection development policy should be encouraged at the school library level; school heads should locate themselves at the centre of the school library activities because such efforts are mostly rewarding hence the duo should collaborate; schools are encouraged to recruit well-trained librarians and support them in their effort to further improve their skills and competence; and teacher/school librarians’ curricula should be tailored in line with the identified millennium challenges. This paper concluded that only those librarians that are receptive to professional developments would be able to cope with the future dictates of the librarianship profession.